FAMILY RISK DURING THE TREATMENT OF PATIENTS WITH TUBERCULOSIS: A QUALITATIVE STUDY OF THE SOCIAL-SUBJECTIVE APPRECIATION OF PATIENTS CARED FOR IN A FIRST-LEVEL OF CARE ESTABLISHMENT - Pérez Siguas, Rosa (2020)
Objectives: To understand the socio-subjective appreciation of patients regarding the family impact during their tuberculosis treatment in a primary care facility. Materials and methods: The population was made up of 12 people who are undergoing antituberculous treatment in a first-level care facility in northern Lima. The technique used was focus group and the instrument used was a semi-structured interview based on the objectives and research categories. Results: 10 heads of household were interviewed, average age 37.5 years, most of them men. The family typology was mostly extensive and nuclear. In the economic risk category, they expressed that the disease generated abandonment of their work and in other episodes of discrimination. In the biological risk category, they perceive the risk of contagion in the family environment as high, showing fear of contagion from their relatives, with the consequent distancing from them. In the social risk category, they expressed their discomfort because their own family was afraid of being with them, often due to fear of contagion or ignorance of the disease. Conclusions: The patients’ appreciation regarding the family risk during their treatment was not good, especially in the economic sphere. The family is crucial to keeping its members healthy, as well as the dynamic and complex processes of family relationships. Furthermore, its members can have a great impact on the health-seeking behavior of members with tuberculosis.